Challenges to Assessing Same-Sex Relationships under Refugee Law in Canada - Hersh, Nicholas (McGill Law Journal / Revue de droit de McGill, 2015)
This article suggests that there are reasons to be concerned about the way relationship history impacts credibility assessments for refugee claims based on sexual orientation. Decision makers’ written assessments often reveal insufficient consideration of the psychosocial barriers that may impinge on sexual minority refugees’ ability to testify on their relationships. The multinational and multicultural setting of refugee-status proceedings poses unique challenges for sexual minority refugee claimants in having their membership in a particular social group established. Understanding and expressing sexual identity spans cultural divides, and therefore, a claimant’s expressed identity may not match the decision maker’s expectations. Notions of love and intimacy may also be culturally construed, and therefore expectations of how these notions manifest in long-term relationships may be inappropriate in the context of refugee status determination.This article emphasizes that implausibility findings concerning claimants’ relationships should be made cautiously. Decision makers should not assume that sexual minorities in countries in which homosexuality is stigmatized or criminalized are devoid of the volition to have same-sex partners. Nor should they assume that sexual minority refugees are necessarily willing to embrace same-sex relationships soon after arriving in Canada. Evaluating same-sex relationships according to the Cass Staged-Identity model can lead to persistent doubts about claimants’ credibility.In sum, this article attempts to canvass the potential pitfalls of Canadian adjudication methods in cases of sexual minority refugee claimants, and to propose recommendations for evaluating testimony and evidence of these relationships.